2015
DOI: 10.1177/0022034515617937
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Proximal Secondary Caries Lesions

Abstract: When choosing detection methods for secondary caries lesions, dentists need to weigh sensitivity, allowing early initiation of retreatments to avoid lesion progression, against specificity, aiming to reduce risks of false-positive diagnoses and invasive overtreatments. We assessed the cost-effectiveness of different detection methods for proximal secondary lesions using Monte Carlo microsimulations. A vital permanent molar with an occlusal-proximal restoration was simulated over the lifetime of an initially 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…These were assessed in a recent review [25], which found that visual, radiographic, and laser fluorescence detection had similar sensitivities and specificities (abilities to detect carious and sound surfaces, respectively), while tactile assessment and light-induced fluorescence are not as useful at present, at least not if used in isolation. There is further data demonstrating that in most low caries risk populations, avoiding false-positive readings and ultimate over-detection and treatment should be prioritized, as secondary lesions progress slowly (see above) and missed lesions may be detected at the next recall consultation [26]. Overall, it seems advisable to combine bitewing radiography (allowing the detection of clinically inaccessible lesions) with visual-tactile assessment (allowing confirmation of findings).…”
Section: Dietary Advicementioning
confidence: 99%
“…These were assessed in a recent review [25], which found that visual, radiographic, and laser fluorescence detection had similar sensitivities and specificities (abilities to detect carious and sound surfaces, respectively), while tactile assessment and light-induced fluorescence are not as useful at present, at least not if used in isolation. There is further data demonstrating that in most low caries risk populations, avoiding false-positive readings and ultimate over-detection and treatment should be prioritized, as secondary lesions progress slowly (see above) and missed lesions may be detected at the next recall consultation [26]. Overall, it seems advisable to combine bitewing radiography (allowing the detection of clinically inaccessible lesions) with visual-tactile assessment (allowing confirmation of findings).…”
Section: Dietary Advicementioning
confidence: 99%
“…In many instances, discolorations or clinically irrelevant imperfections may have been identified as secondary caries [19,30,31]. At present, there is sparse evidence demonstrating what kind of characteristics an identified defect needs to progress into a state where care is undoubtedly needed, or to remain in the status quo in the long term, possibly never progressing and hence never needing care [32].…”
Section: Can We Control Secondary Caries Risk?mentioning
confidence: 99%
“…Given that secondary caries detection is performed as part of a routine screening appointment and possibly applied repeatedly, there is some evidence indicating that specific measures should be prioritized, as secondary caries progresses only slowly and missed lesions may be detected at the next screening round. Alternatively, a sequential usage of sensitive followed by specific methods seems advisable [32]. Avoiding false-positive diagnoses, which lead to costly and invasive overtreatment, seems especially relevant in most of today's low-risk populations.…”
Section: Detecting Secondary Carious Lesionsmentioning
confidence: 99%
“…6 However, the combination of a clinical tactile exam and radiographic evaluation has been shown to be both effective and economical for caries diagnosis. 7 The aim of this study was to assess if the auto calibrating medical grade monitors perform better in comparison to off the shelf and tablet monitors for the identification of artificial incipient caries-like lesions at common primary and secondary caries locations.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%